2015
DOI: 10.1080/01446193.2015.1078901
|View full text |Cite
|
Sign up to set email alerts
|

The effect of leader emotional intelligence on leader–follower chemistry: a study of construction project managers

Abstract: Extending Nicolini's (2002) notion of project 'chemistry', this paper proposes the development of a 'leader-follower chemistry' model associated with the quality of dyadic interpersonal communication in construction projects. The paper focuses on the project manager as leader and attempts to deepen understanding of the effect of a project manager's Emotional Intelligence (EI) on the quality of interpersonal communication with their followers-being other members of the project team. While a project manager's EI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 98 publications
1
16
0
2
Order By: Relevance
“…EI has been suggested to be the 'sin qua non' of leadership (Walter et al 2011), has been generally accepted as essential for effective interpersonal relationships (Pryke et al 2015;Caruso and Salovey 2004), and is relevant in building productive project relationships (Druskat and Druskat 2006). Thus, the concept has been brought to view in construction project management textbooks and analysed in a small number of research articles published in construction journals.…”
Section: Ei In the Construction Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…EI has been suggested to be the 'sin qua non' of leadership (Walter et al 2011), has been generally accepted as essential for effective interpersonal relationships (Pryke et al 2015;Caruso and Salovey 2004), and is relevant in building productive project relationships (Druskat and Druskat 2006). Thus, the concept has been brought to view in construction project management textbooks and analysed in a small number of research articles published in construction journals.…”
Section: Ei In the Construction Industrymentioning
confidence: 99%
“…There is a dearth of general understanding about EI in the construction industry (Pryke et al 2015;Zhang and Fan 2013) and the constant debates on the relevance and the application of EI for construction professionals/ project managers (Mischung et al 2015;Lindebaum and Cassell 2012), signify that the area still requires further development in relation to the context of construction. Although the predominance of a positivist approach into investigating the concept has been identified as one of the possible drawbacks of its development (Lawani 2016), more minutiae in relation to the utilization and practical benefits of EI is still required.…”
Section: Ei In the Construction Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…The study reveals how "Positive Meaning" (creating something), "Positive Emotions" (humour and optimism), "Positive Relations" (collaboration) and "Signature Strengths" (emotional intelligence) can create positive results within a project. These emotional elements play a major role in the development and trajectory of relationships within project settings (Pryke et al 2015).…”
Section: Leadership Demands In Constructionmentioning
confidence: 99%
“…Researchers (Pryke, Lunic, & Badi, 2015;Rehman, 2011;Sunindijo, Hadikusumo, & Ogunlana, 2007) have concluded that emotional intelligence is valuable in a leader-devotee correspondence as it prompts project execution. Rezvani et al (2016) found a significant relationship between project managers' emotional intelligence and project success with the mediating role of job satisfaction and trust in the Australian Defense industry.…”
mentioning
confidence: 99%